PEMANFAATAN BAHAN PANGAN LOKAL DALAM PRODUK PASTRY DI PRIMA IN HOTEL MALIOBORO YOGYAKARTA - Ayu Mawar Saraswati; Titik Sulistyani (Jurnal Socia Akademika, 2020)
ABSTRACTThe purpose of this research is to find out the utilization of local foodstuffs in pastry products atPrima In Hotel Malioboro Yogyakarta. The method used in this research is research in the form of fieldstudies and library studies. Data collection through observation, interviews and documentation. Localfoodstuffs that are used as Pastry products at Prima In Hotel Malioboro are made from very easy-to-accessingredients, one of which is local foodstuffs such as bananas, purple yams, and cassava which are thenprocessed into more quality food and more have a distinctive taste and become food that can be consumedfor hotel guests. Local foodstuffs are utilized in the manufacture of pastry products in the form of cake,namely banana cake, purple yam cake, purple yam brownies and green cassava steamed sponge.Utilization of local foodstuffs as pastry products namely 1) banana sponge/banana cake made fromcrushed bananas first and then mixed with cake dough, 2) purple sweet potato cake and purple sweet potatobrownies from purple yams boiled first and then mashed and mixed with cake dough, 3) steamed spongegreen cassava from shredded cassava first and then squeezed in the juice and then mixed with steamedsponge dough.